2019
DOI: 10.1099/jmm.0.001016
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of Erysipelothrix rhusiopathiae in blood from infected chickens – addressing challenges with detection of DNA from infectious agents in host species with nucleated red blood cells

Abstract: Purpose The present study aimed to establish pretreatment protocols as well as real-time and droplet digital polymerase chain reaction (PCR) methodologies to detect and quantify Erysipelothrix rhusiopathiae (ER) DNA in blood samples from infected chickens, as tools for routine diagnostics and monitoring of experimental infections. Chicken blood is a problematic matrix for PCR analysis because nucleated erythrocytes contribute large amounts of host DNA that inhibit amplification.Methodology Using artificially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 28 publications
4
17
1
Order By: Relevance
“…In the present study vaccination of chickens induced a more effective elimination of ER since the recovery of bacteria in blood was clearly reduced compared to that in naïve chickens [20]. Moreover, the acute innate responses in vaccinated chickens were of much shorter duration compared to those in naïve chickens.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…In the present study vaccination of chickens induced a more effective elimination of ER since the recovery of bacteria in blood was clearly reduced compared to that in naïve chickens [20]. Moreover, the acute innate responses in vaccinated chickens were of much shorter duration compared to those in naïve chickens.…”
Section: Discussionmentioning
confidence: 46%
“…It thus seems likely that these cells serve a role in the chicken defence against ER infection, both as sentinel cells and regulators of immune responses and as potential effector cells killing ER bacteria. We have indeed shown that when ER was incubated in chicken blood in vitro ER DNA was primarily detected in a leukocyte preparation of blood cultures and not free in plasma and that a significant amount of the bacteria recovered in chicken blood during the acute phase of ER infection were intracellular in leukocytes [20]. Hence, the heterophils may have a role phagocytosing ER in analogy with what has been observed for their mammalian counterparts where phagocytosis and killing of ER in vitro has been shown in porcine and murine neutrophils [14].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations